2012
DOI: 10.1111/j.1460-6984.2011.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative skill and syntactic complexity in school‐age children with and without late language emergence

Abstract: These data suggest that children with a history of LLE may exhibit age-appropriate performance on a standardized narrative test, but still lack the syntactic complexity of their TD peers in conversation. Assessments for school-age children with a history of language delay should include analysis of syntactic complexity in conversation to identify continuing weakness. Future research should examine use of other specific types of complex structures (e.g. infinitival and clausal complements) in this population, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
3
17
0
4
Order By: Relevance
“…Redmond (2011) found a similar discrepancy for children with PLI, but the comparison with TD had a larger discrepancy, with comprehension exceeding production by 1.05 SDs. Domsch et al (2012) reported TNL comprehension and production scores for a group of late talkers and an age-matched control group of children who were not late talkers. For the late talkers, comprehension exceeded production by 1.03 SDs, but for the control group, this discrepancy was only 0.63 SD.…”
Section: Receptive-expressive Discrepancies In Narrativesmentioning
confidence: 99%
“…Redmond (2011) found a similar discrepancy for children with PLI, but the comparison with TD had a larger discrepancy, with comprehension exceeding production by 1.05 SDs. Domsch et al (2012) reported TNL comprehension and production scores for a group of late talkers and an age-matched control group of children who were not late talkers. For the late talkers, comprehension exceeded production by 1.03 SDs, but for the control group, this discrepancy was only 0.63 SD.…”
Section: Receptive-expressive Discrepancies In Narrativesmentioning
confidence: 99%
“…These children are widely referred to as Late Talkers (LT) in the literature (Rescorla & Dale, 2013). A substantial number of LTs move into the typical range on standardised language measures during the preschool period, but a subset continues with language impairments throughout the school years (Domsch et al, 2012;Ellis & Thal, 2008;Henrichs et al, 2011;Moyle, Weismer, Evans, & Lindstrom, 2007;Paul & Roth, 2011;Rescorla, 2011;Westerlund, Berglund, & Eriksson, 2006). LTs do not constitute a homogeneous group but present with varied profiles of language and/or social communication skills and deficits which change over time: some present with expressive language problems only, whereas others also evidence limited receptive language and/or social communication skills that border on Autism Spectrum Disorders (ASD) (Desmarais, Sylvestre, Meyer, Bairati, & Rouleau, 2008;Ellis & Thal, 2008;Hawa & Spanoudis, 2014;Paul & Ellis Weismer, 2013;Paul & Roth, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the small sample size, it is important to note that the strict diagnosis criteria of SLI often make it difficult to use big samples, thus, many studies of children with this disorder have a limited number of participants (e.g., Acosta, Moreno, & Axpe, 2012;Anderson & Souto, 2005;Contemori & Garraffa, 2010;Domsch et al, 2012;Marinellie, 2004).…”
Section: Methods Participantsmentioning
confidence: 99%